Investigação das consultas ambulatoriais do HUSM através da estatística multivariada - De Gregori, Jussara Maria (2006)
Public health in Brazil presents many difficulties, and within this challenging context the University Hospital of Santa Maria (HUSM) RS, Brazil makes an effort to maintain its organization by keeping the focus on the efficiency of the healthcare services offered. Based on this fact, the present research aimed to investigate the number of appointments made at the ambulatories of HUSM during the years 2003 and 2005 using multivariate statistical techniques. Specific health areas, which offered ambulatory services, were selected based on the highest number of appointments for patients from the central region of Rio Grande do Sul State. Clustering and factorial analysis, carried out through the principal components, were multidimensional techniques used as a way to detect any relationship in the group of specific clinical areas considered in the study as well as the city where the patients came from. This way, the profile of the ambulatory services at HUSM, which are also offered by specialized clinics, is presented. The findings showed a significant number of patient sent to clinical surgery as well as to treatment with medication or supportive treatment. Among the 33 cities selected, 20 presented a more significant impact regarding appointments at the ambulatories. Therefore, cluster analysis and factorial analysis carried out through the principal components helped to show a relationship between the appointments of specific clinical areas at the ambulatories and the cities of the central region of the State of Rio Grande do Sul, providing support for the improvement of the quality of these services.